Drugs, money, and secret handshakes : the unstoppable growth of prescription drug prices / Robin Feldman. - Feldman, Robin (Cambridge University Press, 2024)
In the warped world of prescription drug pricing, generic drugs can cost more than branded ones, old drugs can be relaunched at astronomical prices, and low-cost options are shut out of the market. In Drugs, Money and Secret Handshakes, Robin Feldman shines a light into the dark corners of the pharmaceutical industry to expose a web of shadowy deals in which higher-priced drugs receive favorable treatment and patients are channeled toward the most expensive medicines. At the center of this web are the highly secretive middle players who establish coverage levels for patients and negotiate with drug companies. By offering lucrative payments to these middle players (as well as to doctors and hospitals), drug companies ensure that inexpensive drugs never gain traction. This system of perverse incentives has delivered the kind of exorbitant drug prices - and profits - that everyone loves except for those who pay the bills.